Perceptions of nursing competence - Armstrong, Susan J (My University, 2016)
A qualitative research study has been carried out in order to determine Perceptions of NUrsing Competence. A critical incident technique 'Was used to collect data from patients to determine the cri ter,,:1a used by them in judging whether a nurse is cmnpetent 'or not. This data was analysed by means of a. .cont.ent;analysis, and the findings compared with the available literature and with the r~.quirements of the South African Nursi)l>gCouncil. This study was done in order to dete'!:'millwehether a set of criteria can be developed from the per~eptions of the patients with regard to nUrsing - competence, with the long term aim of designing all evaluation tool based on these criteria. The study was carried out in a large teaching hospital in Johannesburg by means of interViewing in"'patients in selected 'Ylardsinvolved in student training. Five categories were developed rlPom the data which Were built up froln recording units and themes. In. comparing the, findings of the study to the literature, consensus was found to exist between the patients 6riteria and those of nur-se authors. )\ ()